2020
DOI: 10.3390/ijerph17176071
|View full text |Cite
|
Sign up to set email alerts
|

How to Achieve a Healthier and More Sustainable Europe by 2040 According to the Public? Results of a Five-Country Questionnaire Survey

Abstract: The aim of this paper is to understand public preferences for several future scenarios of achieving a healthier, more equitable and sustainable Europe, which differ in the way the society is organized (individualistically vs. collectively) and in the driving sector (public vs. private). To achieve this aim, we conducted a questionnaire survey using representative samples for five European countries in 2018. About three thousand respondents chose among the four scenarios presented within four different contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Katz-Gerro et al (2017) used four value types (biospheric value, universalism, benevolence and conformity) to explain the engagement in different forms of environmental behaviours, including environmental philanthropic behaviour [23]. Zverinová and her colleagues found that biospheric and egoistic value orientation is useful for examining preferences for healthier and more environmentally friendly scenarios [24].…”
Section: Values and Responsible Managementmentioning
confidence: 99%
“…Katz-Gerro et al (2017) used four value types (biospheric value, universalism, benevolence and conformity) to explain the engagement in different forms of environmental behaviours, including environmental philanthropic behaviour [23]. Zverinová and her colleagues found that biospheric and egoistic value orientation is useful for examining preferences for healthier and more environmentally friendly scenarios [24].…”
Section: Values and Responsible Managementmentioning
confidence: 99%
“…PROVE subscribers are compared with non-subscriber participants in the INHERIT survey of attitudes, preferences and behaviours related to consuming, moving and living. The formulation of the respective items took into account previous studies and was then validated in a pre-study phase (23) – details in Supplemental Materials Table .…”
Section: Methodsmentioning
confidence: 99%
“…The INHERIT Five-Country Survey constitutes one component of an international study on the attitudes, preferences and behaviours related to consumption, mobility and housing (23) . Paid online panels compose the INHERIT Survey sample, targeting representative samples of the adult population of the five countries involved by quota sampling.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations